The Reverse Gear of Logistics - Cezar Radu COJOCARIU (Revista de Management Comparat International)
It is no surprise that almost every company is looking for ways to increase sales, decrease costs and reduce risks. But in such tough economic times, the easy cuts have been made and all of the simple process improvements have been put in place. Enter reverse logistics, an often overlooked process that can help companies reduce waste and improve profits. And yet reverse logistics seldom receive much attention — that is, until something goes wrong. Many executives go out of their way to avoid dealing with returns because it can be ugly and is thought of as nothing more than a cost of doing business. If ignored, critical reverse logistics functions can cost companies millions in lost profits due to damaged customer relationships and external liabilities that could have an enormous impact on their business. Effectively managed, however, reverse logistics can enable organizations t